First catch your market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
workshop was held in Entebbe, Uganda from 2 to 6 November 1998, 'Strategies for strengthening small scale-food processing enterprises in Eastern and Southern Africa'